Capital as Will and Imagination : Schumpeter's Guide to the Postwar Japanese Miracle - Metzler, Mark, 1957- (Book collections on Project MUSE., 2013)
With this book, the author continues his investigation into the economic history of twentieth-century Japan that he began in Lever of Empire. In this book, he focuses on the successful stabilization of Japanese capitalism after the Second World War. How did a defeated and heavily damaged nation manage reconstruction so rapidly? What economic beliefs resulted in the "miracle" years of high-speed economic growth? The author argues that the inflationary creation of credit was key to Japan's postwar success - and its eventual demise due to its instability over the long term. To prove his case, he explores heterodox ideas about economic life, in particular Joseph Schumpeter's realization that inflation is intrinsic to capitalist development. Schumpeter's ideas, widely ignored within standard American neoclassical economic theory, were shaped by his experience of Austria's reconstruction after 1918. They were highly influential in Japan, and the author traces their impact in the period from the Allied Occupation, starting in 1945, through the Income Doubling Plan of 1960. Japan after defeat, the author argues, illustrates the critical importance of inflationary credit creation for increased production. -- Publisher's website.